Phase I trial of volasertib, a Polo‐like kinase inhibitor, in Japanese patients with acute myeloid leukemia. Issue 11 (21st October 2015) - Kobayashi, Yukio; Yamauchi, Takahiro; Kiyoi, Hitoshi; Sakura, Toru; Hata, Tomoko; Ando, Kiyoshi; Watabe, Aiko; Harada, Akiko; Taube, Tillmann; Miyazaki, Yasushi; Naoe, Tomoki
Abstract : This phase I trial conducted in Japanese patients with acute myeloid leukemia evaluated the safety, maximum tolerated dose and pharmacokinetics of volasertib (BI 6727), a selective Polo‐like kinase inhibitor. The primary endpoints were the maximum tolerated dose of volasertib and the incidence of dose‐limiting toxicities. Secondary endpoints were best response and remission duration. Other endpoints included safety and pharmacokinetics. Patients who were ineligible for standard induction therapy or with relapsed or refractory disease received volasertib monotherapy as a 2‐h infusion on days 1 and 15 of a 28‐day cycle, with dose escalation following a 3 + 3 design. A total of 19 patients were treated with three volasertib doses: 350, 400 and 450 mg. One patient receiving volasertib 450 mg reported a dose‐limiting toxicity of grade 4 abnormal liver function test and 450 mg was determined as the maximum tolerated dose. The most frequently reported adverse events were febrile neutropenia (78.9%), decreased appetite (42.1%), nausea and rash (36.8% each), and sepsis, fatigue, hypokalemia, stomatitis and epistaxis (26.3% each). Best responses were complete remission ( n = 3), complete remission with incomplete blood count recovery ( n = 3) and partial remission ( n = 1). The median remission duration of the six patients with complete remission or complete remission with incomplete blood count recovery was 85 days (range 56–358). Volasertib exhibited multi‐compartmental pharmacokinetic behavior with a fast distribution after the end of infusion followed by slower elimination phases. Volasertib monotherapy was clinically manageable with acceptable adverse events and anti‐leukemic activity. Abstract : Plasma concentration of volasertib.